Peran Kualitas Kehidupan Kerja dalam Memediasi Pengaruh Pelatihan dan Karakter Individu terhadap Kinerja Karyawan - Ichsandi Afrizal Muhtadin; Muhammad Halim Maimun (Jurnal Ilmu Manajemen, 2025)
This study aims to examine the extent to which training and individual character affect employee performance, considering the role of quality of work life as a mediating variable in the relationship. This study was conducted at the Department of Housing and Settlement Areas with a quantitative approach, by distributing questionnaires to 150 respondents. The sampling technique used was probability sampling. Data processing was carried out using the Structural Equation Modeling (SEM) approach assisted by SmartPLS software. The results of this study reveal that training and individual character have a significant and positive influence on employee performance, both directly and through the intermediary of quality of work life. Quality of work life has been shown to act as a mediator that strengthens the influence between training and individual character on improving performance. Thus, this study highlights the importance of providing appropriate training, forming a strong work character, and creating a supportive work climate as the main strategies in efforts to improve employee performance, especially in public sector agencies.